Europeanization of environmental policy in the new Europe beyond conditionality - Braun, Mats (Ashgate Pub., 2014)
In this book, Mats Braun offers an up-to-date account of how post-communist member states have handled policy initiatives in the field of environmental policy after accession. Using detailed case studies of how Bulgaria, Czech Republic, Poland and Romania dealt with two different EU policy initiatives; REACH and the Climate-Energy Package.